Incidence of opiates, amphetamines, and cocaine in hair and blood in fatal cases of heroin overdose - Kronstrand, Robert; Grundin, Robert; Jonsson, John (Forensic science international, 1998)
The purpose of the present study was to investigate the occurrence in hair, of some drugs of abuse in deaths caused by heroin overdose, in comparison to findings in blood. Blood, urine and hair samples were obtained during routine post mortem examinations. Samples were analysed for amphetamines, opiates, and cocaine. Immunometric drug screening was performed in urine and positive results confirmed with gas chromatography–mass spectrometry (GC–MS) of blood samples. All hair samples were analyzed with GC–MS. Hair samples were either incubated with methanol for determination of opiates and cocaine, or dissolved in sodium hydroxide for determination of amphetamines. All 19 blood samples were positive for morphine (0.04–0.4 μg g −1) and ten were also positive for 6-acetylmorphine (0.003–0.02 μg g −1). Thirteen of the hair samples were positive for 6-acetylmorphine and seven of which were positive also for morphine. Concentrations ranged from 0.3–7.4 and 0.3–1.3 (ng mg −), respectively. Amphetamine was found in three blood samples (0.04–1.2 μg g −1) and in eleven hair samples (0.4–18.3 ng mg −). Cocaine was determined in one blood sample (0.03 μg g −1) and two hair samples (0.7–6.5 ng mg −). Out of the nineteen cases studied, eight showed chronic multi drug use on the basis of the results of hair analysis. In six subjects no opiates could be detected in hair, suggesting; “first” or occasional intake of heroin, which could be a contributing factor to the overdose death, because of lack of tolerance. We conclude that analysis of hair can be a useful complement to analysis of more conventional autopsy material, especially when investigating overdose deaths and previous histories of drug use and abuse.